1995
DOI: 10.1046/j.1471-4159.1995.64010332.x
|View full text |Cite
|
Sign up to set email alerts
|

Production of Polyclonal Antisera that Recognize and Distinguish Between the Extracellular Domains of Neuronal Nicotinic Acetylcholine Receptor Subunits

Abstract: Ligand-gated ion channels are oligomeric transmembrane proteins that usually contain more than one kind of monomer. The variety of monomers available to participate in olígomer formation and the apparent latitude in acceptable monomer combinations allows considerable diversity. Mechanisms for identifying the monomers comprising specific receptors are needed . We have generated affinity-purified polyclonal antisera that recognize the extracellular domain of nine neuronal nicotinic acetylcholine receptor (nAChR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…(2001)]. Similarly, immunoblotting experiments with a number of affinity‐purified polyclonal antibodies showed that they reacted only with their homologous bacterially expressed proteins and synthetic peptides [e.g., Neff et al. (1995); Chen and Patrick J (1997)].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2001)]. Similarly, immunoblotting experiments with a number of affinity‐purified polyclonal antibodies showed that they reacted only with their homologous bacterially expressed proteins and synthetic peptides [e.g., Neff et al. (1995); Chen and Patrick J (1997)].…”
Section: Discussionmentioning
confidence: 99%
“…Western blot analyses of nAChR subunits expressed in oocytes and transfected fibroblasts (M10) demonstrated that numerous monoclonal antibodies (e.g., a4: mAb299; a7: mAb319; b2: mAb270, mAb290) do not cross-react with other nAChR subunits [e.g., Conroy et al (1992); Wang et al (1996);Schröder et al (2001)]. Similarly, immunoblotting experiments with a number of affinitypurified polyclonal antibodies showed that they reacted only with their homologous bacterially expressed proteins and synthetic peptides [e.g., Neff et al (1995); Chen and Patrick J (1997)]. Moreover, cell lines such as human neuroblastoma IMR32 (Gotti et al 1995) and SH-SY5Y (Martin-Ruiz et al 1999;Guan et al 2000), human embryonic kidney HEK293 cells (Sallette et al 2005) as well as mouse fibroblast cell line M10 (Guan et al 2000) were immunolabeled with nAChR antibodies -among which were Ab-607, sc-1771 (both a3), mAb299, sc-1772, NRa4-1.5 (all a4); mAb306, sc-1447 (both a7) and sc-1449 (b2)-when stably expressing the respective nAChR subtype, but not when untransfected.…”
Section: Discussionmentioning
confidence: 99%
“…Samples were resolved with SDS-polyacrylamide gel electrophoresis (4% stacking, 8% separating gels) transferred to Immobilon membrane (Millipore, Bedford, MA), and immunodetected with antibodies specific for the extracellular domain of the ␣7 nAChR subunit (31,32). All antibodies were diluted in PBS, 0.1% Tween 20, and 5% nonfat dry milk.…”
Section: Quantification Of Receptorsmentioning
confidence: 99%
“…The capsid is comprised of the major capsid protein VP1 and the minor capsid proteins VP2 and VP3 (Watanabe et al, 2013 )]. The α3 nAChRs, α4 nAChRs and β2 nAChRs have been shown to be expressed on the surface of COS-7 cells (Neff et al, 1995 ). In addition to these common cells, other cells are also adopted in AD research, such as NT2-N, which is derived from the human teratocarcinoma cell line NT2 (ATCC ® CRL-1973 TM ).…”
Section: In Vitro Cellular Models Used In Parallel With Pc12...mentioning
confidence: 99%